2019
DOI: 10.5114/biolsport.2018.78904
|View full text |Cite
|
Sign up to set email alerts
|

Maximal power production as a function of sex and training status

Abstract: Maximal muscular power is achieved at lower percentages of maximal strength (1RM); however, this notion has not been elucidated based on sex or training status. Therefore, the purpose of this investigation was to examine the influence of sex and training status on maximal power production. Sixty men and women (resistance trained or untrained) completed 1RM testing for the two-leg press (2LP) and bench press (BP). Participants then returned to perform single repetitions at 20, 30, 40, 50, 60, 70 and 80% of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…Further, biomechanical analysis (differences in upper limbs joint angles and moment arms) and electromyography of the lifting technique were not recorded, and no direct physiological variables were assessed which could help explain the obtained results. As the power production and muscular activity patterns relate to sex and training status, the findings of this study should be generalized with caution (Gołaś et al, 2018;Miller et al, 2019). Therefore, future studies should provide a detailed comparison of the velocity-load relationship in the multi-set bench press exercise protocols with a cambered and standard bar, in a large number of experienced strengthtrained athletes.…”
Section: Discussionmentioning
confidence: 92%
“…Further, biomechanical analysis (differences in upper limbs joint angles and moment arms) and electromyography of the lifting technique were not recorded, and no direct physiological variables were assessed which could help explain the obtained results. As the power production and muscular activity patterns relate to sex and training status, the findings of this study should be generalized with caution (Gołaś et al, 2018;Miller et al, 2019). Therefore, future studies should provide a detailed comparison of the velocity-load relationship in the multi-set bench press exercise protocols with a cambered and standard bar, in a large number of experienced strengthtrained athletes.…”
Section: Discussionmentioning
confidence: 92%
“…Although the 1RM is commonly used in resistance exercise methodology, previous testing procedures to assess 1RM in a standardized manner do not provide specific guidelines related to the movement tempo or the duration of particular phases of the exercise (eccentricconcentric) (Mike et al, 2017;Seo et al, 2012; Journal of Human Kinetics -volume 72/2020 http://www.johk.pl et al, 2018a), which can be problematic in terms of using different tempos in the periodization process. Furthermore, some previous studies showed that maximal strength and power output production depend on training status (Miller et al, 2018) and motivation (Maszczyk et al, 2019(Maszczyk et al, , 2020. Movement tempo is often defined as the pace, cadence or lifting speed of a resistance exercise (Wilk et al, 2018a(Wilk et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is very important due to the need to reduce the high frequency of injuries in the group of women compared to men [ 2 , 5 , 6 , 30 ]. This is especially important because the number of women involved in either professional or recreational sports has been significantly rising in recent years [ 31 , 32 , 33 ]. In the present study, the analysis concerned strength abilities taking into consideration GH/IGF-1 axis hormone levels and collagen metabolism during the menstrual cycle in women involved in moderate-intensity physical activity.…”
Section: Discussionmentioning
confidence: 99%